Just for the summer - Jimenez, Abby (Forever, 2024)
"Justin has a curse, and thanks to a Reddit thread, it's now all over the internet. Every woman he dates goes on to find their soul mate the second they break up. When a woman slides into his DMs with the same problem, they come up with a plan: They'll date each other and break up. Their curses will cancel each other's out, and they'll both go on to find the love of their lives. It's a bonkers idea... and it just might work. Emma hadn't planned that her next assignment as a traveling nurse would be in Minnesota, but she and her best friend agree that dating Justin is too good of an opportunity to pass up, especially when they get to rent an adorable cottage on a private island on Lake Minnetonka. It's supposed to be a quick fling, just for the summer. But when Emma's toxic mother shows up and Justin has to assume guardianship of his three siblings, they're suddenly navigating a lot more than they expected--including catching real feelings for each other. What if this time Fate has actually brought the perfect pair together?"--